Detection of hemoglobinopathies in patients of anaemia using high performance liquid chromatography (HPLC) - a hospital based prospective study - Dr. Mahesh Kumar U; Miss. Devisri Y (Tropical Journal of Pathology and Microbiology, 2019)
Introduction: In India, the gene frequency of hemoglobinopathies is 4.2%, with a population over 1 billion and over 12000 infants born each year have a clinically significant hemoglobinopathies. In various parts of India, the prevalence of β-Thalassemia is different. β- Thalassemia has a high prevalence in some communities, such as Sindhi, Luvana, Tribes, and Rajputs. There is no such study done in and around Karimnagar district of Telangana state, therefore a preliminary hospital-based study was carried out. Materials & Methods: In this cross-sectional hospital-based study, target group adopted was anaemic patients (<11gm/dl). Haemoglobin and Red Blood Cell indices were measured on automated– three part differential cell counter. All these samples were analysed for haemoglobin disorders by BIORAD ‘VARIANT’ HPLC machine. Results: Among the cases, Karimnagar (62), Adilabad (143) and Medak (15) districts amounting for 220 cases in which 36 (16.36%) were having Hemoglobinopathies of which Karimnagar had 12 cases, Adilabad 23 cases and Medak had one case. The present study also revealed the prevalence of hemoglobinopathies according to caste. Mala caste had a higher frequency 12/36 (33.3%) followed by Munnur Kapu 6/36 (16.6%) and Christians 5/36(13.8%). This might be due to higher population of mala community as compared to others reported to the hospital. Conclusion: The data regarding prevalence and distribution can be useful in prevention and management of various hemoglobinopathies which may play a vital role in the hospital blood bank as well as in the formulation of transfusion policies.